Clinical Outcomes Associated with Appropriate Use of Percutaneouscoronary Intervention - Najmi Fauzan Tarsidin; Panji Fortuna Hadisoemarto; Noormarina Indraswari; Lusiana Siti Masytoh; Badai Bhatara Tiksnadi (Lembaga Publikasi Ilmiah Nusantara, 2026)
The Appropriate Use Criteria (AUC), developed by the American College of Cardiology Foundation, serve as a guideline to optimize patient selection for percutaneous coronary intervention (PCI); however, their association with clinical outcomes remains unclear. This systematic review examines the relationship between AUC classification and clinical outcomes in patients undergoing PCI for stable ischemic heart disease and acute coronary syndrome, based on publications retrieved from The Cochrane Library, EMBASE, and MEDLINE from January 2009 to October 2024, including studies utilizing the 2009 and 2012 AUC versions as well as a country-specific adaptation. Five studies comprising 55,687 patients met the inclusion criteria. Two studies assessed short-term and in-hospital clinical outcomes; one reported a higher incidence of major adverse cardiovascular events (MACE) among patients receiving inappropriate PCI. At the same time, the other found no significant impact of AUC classification on short-term outcomes. Regarding long-term outcomes, three out of four studies found no significant association between AUC classification and long-term clinical outcomes. Taken together, the available evidence remains limited and inconsistent, underscoring the need to refine the AUC framework further to ensure a more evidence-based approach to guiding patient selection and improving outcomes among patients undergoing PCI.